Digital Eye strain among Undergraduate Medical students of Nepal Medical College and Teaching Hospital during COVID-19 Pandemic (Nepal Medical College Journal, 2022)
During Covid-19 Pandemic, there was declaration of lockdown which led to increased usage of digital devices due to starting of online classes. Increased duration of digital device usage predisposed students to Digital eye strain (DES). This study aimed at estimation of the prevalence of DES among medical students of Nepal Medical College and Teaching Hospital during Covid pandemic. It also analyzed the pattern of digital device usage, risk factors for DES, awareness and practice of preventive measures taken by students during online classes. This was a cross-sectional questionnaire-based survey which included one hundred and sixteen undergraduate medical students. The mean age of the students was 22±1.30 years. Sixty-two students (53.4%) were male and fifty-four (46.6%) were female. There was a significant increase in the duration of digital device usage during Covid -period as compared to pre-Covid period (P=